Perceptions of community health nurses on monkeypox cases: A qualitative study - Alhamidah, Murni; Tusrini, Tusrini; Guan, Lian Wah (Science Center Group, 2024)
Background: The recent rise in monkeypox cases has highlighted the urgent need for improved preparedness within healthcare systems, particularly at the community level. Community health nurses play a critical role in early detection, prevention, and outbreak management; however, emerging infectious diseases such as monkeypox pose new challenges related to knowledge gaps, emotional responses, and system readiness. Objective: This study aimed to explore community health nurses’ perceptions, knowledge, and preparedness in managing monkeypox cases. Methods: A qualitative descriptive study design was employed. Semi-structured interviews were conducted with community health nurses working in primary health care centers in. Participants were selected using purposive sampling based on their involvement in community health and infectious disease services. Data were analyzed using thematic analysis to identify key patterns and themes related to nurses’ experiences and preparedness in managing monkeypox. Results: Four main themes emerged: awareness and knowledge of monkeypox, perceived risk and emotional response, preparedness and training needs, and barriers to effective response. Although most nurses demonstrated general awareness of monkeypox, gaps in disease-specific knowledge and practical training were evident. These limitations contributed to feelings of anxiety, uncertainty, and reduced confidence in managing potential cases. In addition, systemic barriers such as delayed resource allocation and inconsistent communication were identified as factors hindering effective outbreak response. Conclusion: Community health nurses’ preparedness to manage monkeypox remains suboptimal due to gaps in knowledge, training, and system support. Strengthening preparedness through targeted education, improved access to resources, and clear communication mechanisms is essential to enhance outbreak response and support community health nurses in managing future emerging infectious diseases.